Malayalam Intermediate Course Language Laboratory Materials - (:unkn) unknown (My University, 2019)
This book covers all the basic and functional structures of Malayalam and introduces in a graded manner. The primary objective of this book is to make the learners to be fluent in all the four language skills. Accordingly, the teaching methodology will be followed. The exercises and evaluation strategies are carefully designed and incorporated in the book in order to achieve the objective.
Keywords: Malayalam